The Incidence Rate of Cranii Base Fracture in Dr. Kariadi Hospital Semarang Period 2019 - Nugroho Akhbar; Erie B. P. Setya Budi Andar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Introduction: Head injury is a major cause of death, especially in young adults and a major cause of disability. The incidence of head injuries is increasing due to the increasing use of motorized vehicles. As many as 4% of cases of head fracture occur in the base of the cranii. Method: This research used a descriptive observational method. The data used is secondary data taken from medical records. In this study, we wanted to know the incidence of cranii base fracture cases due to head trauma in patients treated at Dr. Kariadi period 2019. Result: From 29 samples of medical records obtained, 48.3% had mild head trauma, 27.6% had moderate head trauma, and 24.1% had severe head trauma. Symptoms of patients with the most clinical symptoms of cranii base fracture were raccoon eyes 51.7%, with the most fracture locations in the anterior fossa as much as 51.7%. Conclusion: The incidence of cranii fracture due to head trauma at RSUP Dr. Kariadi in 2019 was found mostly over 40 years old and most of them were men. The type of injury is a minor head injury, with the largest location in the anterior fossa, and the most common clinical sign found in patients with cranii fracture is raccoon eyes.